1999
DOI: 10.1006/dbio.1999.9383
|View full text |Cite
|
Sign up to set email alerts
|

Mammalian BMP-1/Tolloid-Related Metalloproteinases, Including Novel Family Member Mammalian Tolloid-Like 2, Have Differential Enzymatic Activities and Distributions of Expression Relevant to Patterning and Skeletogenesis

Abstract: Vertebrate bone morphogenetic protein 1 (BMP-1) and Drosophila Tolloid (TLD) are prototypes of a family of metalloproteases with important roles in various developmental events. BMP-1 affects morphogenesis, at least partly, via biosynthetic processing of fibrillar collagens, while TLD affects dorsal-ventral patterning by releasing TGFbeta-like ligands from latent complexes with the secreted protein Short Gastrulation (SOG). Here, in a screen for additional mammalian members of this family of developmental prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
177
2

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 252 publications
(193 citation statements)
references
References 41 publications
10
177
2
Order By: Relevance
“…Similarly, the vertebrate SOG orthologue Chordin is cleaved in vitro, at two sites (Fig. 5A), and counteracted in overexpression assays in Xenopus and zebrafish embryos, by various BMP1/TLD-like proteinases (Blader et al, 1997;Dale et al, 2002;Piccolo et al, 1996;Scott et al, 1999;Wardle et al, 1999). In mammals, BMP1 and mTLL1, but not mTLD or mTLL2, are capable of cleaving Chordin in vitro ; and products of the Bmp1 and Tll1 genes are responsible for cleaving Chordin in vivo .…”
Section: Bmps 2 Andmentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the vertebrate SOG orthologue Chordin is cleaved in vitro, at two sites (Fig. 5A), and counteracted in overexpression assays in Xenopus and zebrafish embryos, by various BMP1/TLD-like proteinases (Blader et al, 1997;Dale et al, 2002;Piccolo et al, 1996;Scott et al, 1999;Wardle et al, 1999). In mammals, BMP1 and mTLL1, but not mTLD or mTLL2, are capable of cleaving Chordin in vitro ; and products of the Bmp1 and Tll1 genes are responsible for cleaving Chordin in vivo .…”
Section: Bmps 2 Andmentioning
confidence: 98%
“…Subsequent to the finding that BMP1 provides pCP activity (Kessler et al, 1996;Li et al, 1996), it was shown that each of the mammalian BMP1/TLD-like proteinases has some level of pCP activity; with BMP1 and mTLL2 showing highest and lowest in vitro pCP levels, respectively Scott et al, 1999). In fact, mTLL2 pCP levels are not observable in vitro, unless procollagen substrates and mTLL2 are co-incubated in the presence of a third protein known to enhance the pCP activity of BMP1/TLD-like proteinases and see below).…”
Section: Fibrillar Collagensmentioning
confidence: 99%
“…Subsequent work showed that BMP-1 is a smaller spliced variant of mTld (4). The functions of BMP-1 remained unknown until it was shown that it can cleave chordin, an antagonist of BMP-2, which can direct bone and cartilage formation (5).…”
Section: Bmp-1mentioning
confidence: 99%
“…Members of the BMP-1/tolloid family of metalloproteinases cleave chordin at two sites, immediately downstream of vWC1 and -3 (12,13). Tsg can also promote cleavage of chordin by tolloids and has a role in increasing the turnover of chordin fragments (14).…”
mentioning
confidence: 99%